2017
DOI: 10.1093/gbe/evw298
|View full text |Cite
|
Sign up to set email alerts
|

Proteome evolution of deep-sea hydrothermal vent alvinellid polychaetes supports the ancestry of thermophily and subsequent adaptation to cold in some lineages

Abstract: Temperature, perhaps more than any other environmental factor, is likely to influence the evolution of all organisms. It is also a very interesting factor to understand how genomes are shaped by selection over evolutionary timescales, as it potentially affects the whole genome. Among thermophilic prokaryotes, temperature affects both codon usage and protein composition to increase the stability of the transcriptional/translational machinery, and the resulting proteins need to be functional at high temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 88 publications
3
41
0
Order By: Relevance
“…The transcriptomic and Sanger sequences found that Paralvinella is paraphyletic owing to the position of Alvinella. This has been suggested based on a previous study using transcriptomic data, where Alvinella and Paralvinella were not reciprocally monophyletic in all gene trees [69], but an outgroup was missing to fully interpret these results. Here, we showed unequivocally that Paralvinella pandorae and P. irlandei were a sister group to Alvinella and the other Paralvinella species and so should be referred to Nautalvinella, originally a subgenus of Paralvinella that was erected based on gill morphology [70].…”
Section: Discussionmentioning
confidence: 76%
“…The transcriptomic and Sanger sequences found that Paralvinella is paraphyletic owing to the position of Alvinella. This has been suggested based on a previous study using transcriptomic data, where Alvinella and Paralvinella were not reciprocally monophyletic in all gene trees [69], but an outgroup was missing to fully interpret these results. Here, we showed unequivocally that Paralvinella pandorae and P. irlandei were a sister group to Alvinella and the other Paralvinella species and so should be referred to Nautalvinella, originally a subgenus of Paralvinella that was erected based on gill morphology [70].…”
Section: Discussionmentioning
confidence: 76%
“…Given the key and prototypical role of AcNEIL1 in genome repair, we examined the evolutionary conservation of Neil1 and its acetylation center in the two main lineages of bilateria (560–0 Ma), deuterostomes and protostomes. We included the sequence of the polychaete worm A. pompejana , an ancestral extremophile residing in deep-sea hydrothermal vents ( 48 ), which we obtained from partial genome assembly from specimens collected during an expedition on the East Pacific Rise ( Supplementary Figure S10A ). A total of 241/260 species comprising all deuterostomes (540–0 Ma) and Lophotrochozoa (536–0 Ma), and part of the Ecdysozoa clade displayed strong evolutionary conservation (blastp values between 7e −64 and 33 −112 ), although no significant hits were found in Nematoda and Hexapoda, which include the model genomes of Caenorhabditis elegans and Drosophila melanogaster (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…For examples, similar researches were performed on cactophilic Drosophila , and the Tibetan fish Gymnodiptychus pachycheilus to identify potential candidate genes for environmental adaptation [68, 69]. Similarly, comparative transcriptome analysis in alvinellid polychaetes revealed that the trait of thermophilic species that still inhabit higher temperature environments was maintained by purifying selection in lineages, while the trait of lineages currently living in colder habitats was likely obtained under selective relaxation, with some degree of positive selection for low-temperature adaptation at the protein level [70].…”
Section: Discussionmentioning
confidence: 99%